Nanoparticulate drug delivery systems, in vitro drug release test methods. - DEVA PRASAD V, (International Journal of Pharma and Bio Sciences, 2017)
This review summarizes the Nanoparticulate preparation, and different types of nanoparticle formulations for sustained drug delivery, drug release(standard temperature 37âˆ˜C) from nano particulate drug delivery system and establishing IVIVC, Site of administration and site of action of formulation selects the release media for the nanosized dosage forms. Because of no compendial standards exist, drug release is assessed using different methods such as sample and separate method(SS), continuous flow (CF), ), dialysis membrane (DM) methods, and also combination thereof, as well as novel techniques like turbidimetry and voltametry, This review describes the principle of each methods and challenges with setup and sampling, along with their advantages and disadvantages, The SS methods gives the direct measurement of drug release with simple set up requirements but sampling is difficult, with the CF method sampling is straight forward but the setup is time consuming, Set-up as well as sampling is easier with the DM method, but it may not be suitable for the drug that binds to membrane, Novel methods are developed which offers real time drug release measurement, but may be restricted to certain types of drugs. Of these dissolution techniques the Level A IVIVCs have been obtained with dialysis method alone or in the combination with the sample and separate technique. In future some efforts should focus on developing mathematical models that describes drug release mechanism, as well as facilitate formulation development of nanoparticle dosage forms.